Pendidikan Moderasi Beragama di Indonesia - Cahyo Muliawan; Muhammad Fauzan Ahsan Hafizi (STAI Kuala Kapuas, 2024)
At present we Muslims face many kinds of challenges, because of the many conflicts that appear. This happens because there are groups that appear who do not want to accept differences, it can damage the integrity of the Unitary Republic of Indonesia. In order to avoid this damage and to allow interfaith people to live side by side, peacefully and in peace, moderation in religion is needed. The purpose of writing this journal is to explain what religious moderation really is. The research method in this journal is library research, namely research that focuses on the literature using a qualitative approach. The results of this study are able to understand religious moderation correctly, so that it can be applied in daily life, so that there is a safe, peaceful and peaceful life.